Representasi Multikulturalisme dalam Wacana Media Sosial: Analisis Kritis atas Konstruksi Identitas Kolektif - Ahmad Faruq Dzulfikar; Siti Zahrotun Nisa Kamila; Muhammad Wildan Fauzan Hakim (Nalar Bhinneka: Jurnal Humaniora, 2026)
This research is motivated by the increasing use of social media as a space for forming collective identity in Indonesia. Although social media offers potential for multicultural dialogue, the narratives circulating often reinforce polarization and identity-based discrimination. This study aims to analyze the representation of multiculturalism in social media discourse and examine the construction of collective identity formed through online discursive practices. The method employed is critical discourse analysis with an interpretive qualitative approach. Data were collected from Twitter/X, Instagram, and TikTok platforms during the period 2023–2024. The results show that social media discourse predominantly constructs collective identity through in-group and out-group framing, cultural symbolization, and exclusive nationalist rhetoric. The study concludes that the representation of multiculturalism in social media tends to be superficial and instrumentalistic, thus requiring multicultural digital literacy to promote sustainable social cohesion.